Penerapan Pendekatan Ing ngarsa sung Tuladha, ing madya mangun Karsa, Tut wuri Handayani dalam metode pembelajaran Guru PAI - Nila Nilnal Muna; Juniati, Rizqi malia; Slamet Faturrohman; Abdul Hafid Alhaq; Arditya Prayogi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The approaches of Ing Ngarsa Sung Tuladha, Ing Madya Mangun Karsa, and Tut Wuri Handayani are educational concepts introduced by Ki Hajar Dewantara that emphasize the important role of educators as role models, motivators, and guides throughout the learning process. This study aims to describe the implementation of these three approaches in the teaching methods of Islamic Religious Education (PAI) teachers. The method employed is library research by reviewing various journals and literature related to Ki Hajar Dewantara’s educational philosophy and its application in the learning process. The findings of this study indicate that the implementation of Ing Ngarsa Sung Tuladha is reflected in the attitudes and behaviors of PAI teachers, which serve as examples, as well as in the religious values they demonstrate. The Ing Madya Mangun Karsa approach is applied through interactive learning that encourages students’ motivation, creativity, and participation. Meanwhile, Tut Wuri Handayani is manifested in the educator’s role as a facilitator who provides support, guidance, and assistance to students throughout the learning process. The implementation of these three approaches is considered capable of creating a humanistic, active, and character-oriented PAI learning environment. Therefore, Ki Hajar Dewantara’s educational philosophy remains relevant to the teaching methods of PAI teachers in contemporary education.